2002
DOI: 10.2307/1565811
|View full text |Cite
|
Sign up to set email alerts
|

Fecal Testosterone Concentrations May Not Be Useful for Monitoring Reproductive Status in Male Blue-Tongued Lizards (Tiliqua nigrolutea: Scincidae)

Abstract: Assessment of reproductive status in animals generally depends on monitoring hormone concentrations in plasma, but blood sampling often involves significant stress to the subject. Monitoring steroid profiles by assaying excreted steroids in urine and/or fecal samples is non-invasive, but does pose some problems. Unlike plasma assays, urinary and fecal steroid analyses are of relatively little value in monitoring rapid, short-term changes in hormone concentrations (Heistermann et al., 1993) because there is a s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 14 publications
0
8
0
Order By: Relevance
“…Fecal retention is known to influence the concentration of hormone metabolites in feces [Schwarzenberger et al, 1996]. In a study of male blue‐tongued lizards ( Tiliqua nigrolutea ), seasonal variation in feeding frequency and fecal passage time was discussed as the major cause for unreliable results [Atkins et al, 2002]. Pooling of the samples for more than 4 days decreased but may not have completely accounted for individual differences in our study.…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…Fecal retention is known to influence the concentration of hormone metabolites in feces [Schwarzenberger et al, 1996]. In a study of male blue‐tongued lizards ( Tiliqua nigrolutea ), seasonal variation in feeding frequency and fecal passage time was discussed as the major cause for unreliable results [Atkins et al, 2002]. Pooling of the samples for more than 4 days decreased but may not have completely accounted for individual differences in our study.…”
Section: Discussionmentioning
confidence: 79%
“…Because of the difficulties associated with collecting repeated blood samples at frequent intervals from small specimens, most serum profiles were limited to single samples per animals, weekly or monthly samplings from the same individuals, or were associated with sacrificing the animals [Brasfield et al, 2008; Edwards and Jones, 2001; Gavaud, 1986; Holmes and Alison, 2006; Lovern and Wade, 2003; Martinez‐Torres et al, 2003; Moore et al, 1985; Radder et al, 2001; Shanbhag et al, 2001]. A few reptile studies have used noninvasive fecal hormone metabolite monitoring: corticosteroid metabolite analysis in box turtles [Rittenhouse et al, 2005] and gonadal steroid metabolite analysis in tortoises and lizards [Atkins et al, 2002; Casares, 1995].…”
Section: Introductionmentioning
confidence: 99%
“…Variation in excretion rates in conjunction with temporal differences in circulating hormone levels could exacerbate hormone metabolite concentration variability. Atkins et al [2002] found that in blue-tongued lizards fecal production varied by season, and that in times of reduced feces production, fecal testosterone metabolite concentrations were higher. Additionally, length of sample storage before analysis can increase variation in hormone measurements.…”
Section: Discussionmentioning
confidence: 92%
“…Baltic et al , 2005; Goymann, 2005; Möstl et al , 2005; Palme et al , 2005; Wasser & Hunt, 2005; Szoke et al , 2006) and, to a lesser extent, reptile (i.e. Atkins et al , 2002; Rittenhouse et al , 2005), amphibian (Szymanski et al , 2006) and fish (i.e. Turner et al , 2003; Ellis et al , 2004; Wysocki et al , 2006) species.…”
Section: Introductionmentioning
confidence: 99%